Deep brain stimulation for tremor resulting from acquired brain injury. Issue 7 (4th December 2013) - Sitsapesan, H A; Holland, P; Oliphant, Z; De Pennington, N; Brittain, J-S; Jenkinson, N; Joint, C; Aziz, T Z; Green, A L
Abstract : Objectives: To evaluate the efficacy of deep brain stimulation (DBS) in the treatment of tremor resulting from acquired brain injury (ABI). Methods: A series of eight consecutive patients with post-ABI tremor were treated with DBS of the ventro-oralis posterior (VOP)/zona incerta (ZI) region, and subsequently underwent blinded assessments using Bain's tremor severity scale. Results: VOP/ZI DBS produced a mean reduction in tremor severity of 80.75% based on Bain's tremor severity scale, with significant reductions in all five component tremor subscores: rest, postural, kinetic, proximal and distal. No adverse neurological complications were reported, although one patient experienced exacerbation of pre-existing gait ataxia. Conclusion: VOP/ZI stimulation is demonstrated here to be an effective and safe approach for the treatment of post-ABI tremor in the largest series published at the time of writing.